Handbook of Bereavement / Theory, Research and Intervention - Stroebe Margaret (Cambridge University Press, 2008)
A comprehensive review of scientific knowledge on the consequences of losing a loved person through death. Contributors, Preface, Introduction, The Phenomenology and Measurement of Grief, Current Theories of Grief and Mourning and Bereavement, Physiological Changes Following Bereavement, The Psychological and Social and Health Impacts of Conjugal Bereavement, Grief Reactions to Different Types of Loss, Coping and Counselling and Therapy, Conclusions, References, Author and Subject Index.